2015
DOI: 10.5414/cp202176
|View full text |Cite
|
Sign up to set email alerts
|

Tildrakizumab, a novel anti-IL-23 monoclonal antibody, is unaffected by ethnic variability in Caucasian, Chinese, and Japanese subjects

Abstract: The pharmacokinetics of tildrakizumab were similar in Japanese, Caucasian, and Chinese subjects. Tildrakizumab exposure increased proportionally with dose in the range of 50-400 mg. A single SC dose of 50, 200, and 400 mg or a single IV dose of 10 mg/kg was generally well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In a previous study, the PK of tildrakizumab was similar in Japanese, Caucasian and Chinese subjects matched by age, sex, height, body weight and body mass index 23 . Furthermore, in the present study, the Japan region had no impact on the PASI response as a covariate.…”
Section: Discussionsupporting
confidence: 59%
“…In a previous study, the PK of tildrakizumab was similar in Japanese, Caucasian and Chinese subjects matched by age, sex, height, body weight and body mass index 23 . Furthermore, in the present study, the Japan region had no impact on the PASI response as a covariate.…”
Section: Discussionsupporting
confidence: 59%
“…32 Additionally, study on tildrakizumab, a humanized IgG1/k antieinterleukin-23 monoclonal antibody, found no impact of ethnic variability in white, Chinese, and Japanese patients. 33 Finally, a clinical research study by Uenaka et al 34 showed that the PK characteristics of solanezumab were similar in Japanese and white patients, with similar CL and Vd across doses. The findings from these studies together with our findings suggest that ethnicity is unlikely to affect the PK behavior of IgG and monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies on tildrakizumab have shown the development of anti-drug antibodies (ADA) [196,197]. This may have significance in patients that would potentially have to take such therapies over an extended period of time, and therefore this may not be a clinically relevant issue with lung cancer.…”
Section: Expert Opinionmentioning
confidence: 98%